The Effect of Basic Passing Movements In Volleyball Through Playing Bouncing Ball With A Pair Pattern - Luky Apriyana Mahesa; Adang Sudrajat; Dewi Susilawati (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to determine the effect of applying the method quantitatively experimentally with One Group Pretest and Post Test Design. in improving basic volleyball passing techniques at SDN 8 Cicalengka, Cicalengka District, Bandung Regency. Data collection techniques from the pre-test sig normality test = 0.2 Sig value (0.2) > 0.05, the conclusion is that the pretest data is normally distributed. Post-test sig data = 0.11 Sig value (0.11) > 0.05, in conclusion the posttest data is normally distributed, homogeneity test Sig = 0.32 After carrying out a homogeneity test using SPSS, a sig value of (0.32) is obtained, meaning that the sig value (0.6) > 0.05 then the data The test is homogeneous, and the following is the T test H0: There is no result/influence. HI: There is a result/influence. If the sig value is > 0.05 then the HI is rejected. If the sig value is < 0.05 then the HI is accepted. Sig value: 0.001. As for the results of the paired pattern data from the pre-test and post-test normality tests, the results of the homogeneity test using SPSS obtained a sig value of (0.23), meaning that the sig value is (0.6) > 0.05, so the data is homogeneous, and as for the T test, there is H0: None HI results/influence: There are results/influence If the sig value is > 0.05 then the HI is Rejected If the sig value is < 0.05 then the HI is Accepted.